The Politics of Textiles in the Romanian Contemporary Art Scene. (3rd July 2019) - Asavei, Maria Alina
Abstract: This paper explores the means and ends to which textiles are employed by contemporary Romanian artists in their intermedial practices. The history of textile arts in Romania's cultural-political sphere has received little academic attention in studies dedicated to recent history. The argument put forth is that tapestry, rugs, and other textiles associated in the past with undervalued housework or folk art—and ranked as a lower form of artistry in the artistic hierarchy—are reinvested with political, critical, and mnemonic meanings. The first section addresses the convoluted relationship between textile arts and Romania's communist era during Nicolae Ceauşescu's regime by highlighting the ways in which the authoritarian state supervised and controlled the production of so-called folk textile art to political ends. The next sections elaborate on the artistic production of Geta Brătescu, Ana Lupaş, and Ion Grigorescu, all of whom produced contemporary textile art—often derogatively called "applied art"—whose meanings and purposes eluded the official requirements of national folk art. In the last section the paper scrutinizes the political, critical, and artistic comeback of textile arts as cultural memory since the fall of the communist regime in 1989.